Prognostic role of c-Met in head and neck squamous cell cancer tissues: a meta-analysis - Vsiansky, Vit; Gumulec, Jaromir; Raudenska, Martina; Masarik, Michal (Scientific reports, 2018)
This meta-analysis aims to evaluate the effects of high c-Met levels in head and neck squamous cell carcinomas (HNSCC) on survival and clinicopathological features. Publications concerned with the clinical significance of c-Met protein expression in HNSCC were identified from the Scopus and Web of Science database searches. To elucidate the relationship between c-Met expression and clinical outcomes, a meta-analysis of the selected articles was conducted. Seventeen publications involving a total of 1724 patients met the inclusion criteria. c-Met overexpression was significantly correlated with poor overall survival (hazard ratio (HR) = 2.19, 95% confidence interval (CI) = 1.55-3.10). c-Met immunohistochemical staining positivity was also associated with worse relapse-free survival (HR = 1.64, 95% CI = 1.24-2.17) and presence of regional lymph node metastases (odds ratio (OR) = 1.76, 95% CI = 1.26-2.45). High levels of c-Met expression in HNSCC predict unfavorable prognosis associated with common clinicopathological features.
Keywords: lymfatické metastázy; Proto-Oncogene Proteins c-met; Squamous Cell Carcinoma of Head and Neck; Humans; analýza přežití; lidé; Lymphatic Metastasis; dlaždicobuněčné karcinomy hlavy a krku; Prognosis; prognóza; Survival Analysis; protoonkogenní proteiny c-met